Solution‐Processable Carbon Nanotube Nanohybrids for Multiplexed Photoresponsive Devices - Ye, Qingyu; Xu, Xinzhao; Paghi, Alessandro; Bamford, Thomas; Horrocks, Benjamin R; Houlton, Andrew; Barillaro, Giuseppe; Dimitrov, Stoichko; Palma, Matteo (Advanced functional materials, 2021)
Here, the formation of carbon nanotube (CNT)‐based nanohybrids in aqueous solution is reported, where DNA‐wrapped CNTs (DNA‐CNTs) act as templates for the growth of PbS and CdS nanocrystals, toward the formation of PbS‐DNA‐CNT and CdS‐DNA‐CNT heterostructures. Solution‐processed multiplexed photoresponsive devices are fabricated from these nanohybrids, displaying a sensitivity to a broad range of illumination wavelengths (405, 532, and 650 nm). The DNA‐CNT and CdS‐DNA‐CNT devices show a drop in the current while PbS‐DNA‐CNT's current increases upon light illumination, indicating a difference in the operational mechanisms between the hybrids. Furthermore, the ON/OFF photoresponse of PbS‐DNA‐CNT is only 1 s as compared to 200 s for the other two nanohybrid devices. The mechanisms of the different photoresponses are investigated by comparing the performance under an inert and air atmosphere, and gate dependence device analysis and transient absorption spectroscopy measurements are also conducted. The results reveal that photoinduced oxygen desorption is responsible for the slower photoresponse by DNA‐CNT and CdS‐DNA‐CNT, while photoinduced charge transfer dominates the much faster response of PbS‐DNA‐CNT devices. The strategy developed is of general applicability for the bottom‐up assembly of CNT‐based nanohybrid optoelectronic systems and the fabrication of solution‐processable multiplexed devices. The assembly in aqueous solution of carbon nanotube (CNT)‐based nanohybrids is presented, where DNA‐wrapped CNTs are employed as templates for PbS and CdS nanocrystals growth, toward the formation of PbS‐DNA‐CNT and CdS‐DNA‐CNT heterostructures. Solution‐processable mutliplexed photoresponsive nanoscale devices are fabricated from the aforementioned nanohybrids.